Risk of mortality between warfarin and direct oral anticoagulants: population-based cohort studies - Zixuan Wang; Julian Matthewman; John Tazare; Qiuyan Yu; Ka Shing Cheung; Celine S. L. Chui; Esther W. Y. Chan; Krishnan Bhaskaran; Liam Smeeth; Ian C. K. Wong; Ian J. Douglas; Angel Y. S. Wong (BMC Medicine)
Abstract Background Direct oral anticoagulants (DOACs) have been reported to be associated with a higher risk of mortality compared with an older alternative, warfarin using primary care data in the United Kingdom (UK). However, other studies observed contradictory findings. We therefore aimed to investigate the association between mortality and warfarin, compared with DOACs. Methods We conducted cohort studies using UK Clinical Practice Research Datalink (CPRD) Aurum and Hong Kong Clinical Data Analysis and Reporting System (CDARS) to identify the association between warfarin and hazard of mortality, compared to DOACs. Individuals with non-valvular atrial fibrillation aged ≥ 18 years who had first anticoagulant therapy (warfarin or DOAC) during 1/1/2011–31/12/2019 were included. Results Compared with DOAC use, a lower hazard of all-cause mortality was found in warfarin users (hazard ratio (HR) = 0.81, 95% confidence interval (CI) = 0.77–0.86) in CPRD; while a higher hazard was observed in warfarin users (HR = 1.31, 95% CI = 1.24–1.39) in CDARS, versus DOAC users. In our exploratory analysis, consistent results were seen in both databases when stratified warfarin users by time in therapeutic range (TTR) using post-baseline measurements: a lower hazard of all-cause mortality in warfarin users with TTR ≥ 65% (CPRD: HR = 0.68, 95% CI = 0.65–0.72; CDARS: HR = 0.86, 95% CI = 0.77–0.96) and increased hazard in warfarin users with TTR < 65% (CPRD: HR = 1.14, 95% CI = 1.05–1.23; CDARS: HR = 1.59, 95% CI = 1.50–1.69), versus DOAC users. Conclusions The differences in hazard of all-cause mortality associated with warfarin compared with DOAC, in part may depend on anticoagulation control in warfarin users. Notably, this study is unable to establish a causal relationship between warfarin and mortality stratified by TTR, versus DOACs, requiring future studies for further investigation.